DESIGNING A VIRTUAL LABORATORY FOR DEVELOPING ISLAMIC JOURNALISM - Andini Bahri; Fatma Yulia; Saimroh; Nur Sa’adah (Penamas, 2023)
Improvement of student skills can be pursued one of them with practicum activities. Journalism practicum can help students acquire the skills needed by the media industry, such as skills as journalists, editors and layouters. However, from its inception the UINSU KPI Study Program never had a laboratory, especially for online journalism courses. Therefore, the aim of this research is to design a virtual laboratory in the form of a news portal and online magazine as a practicum facility for KPI UINSU students. This research method is Research and Development which starts from problem identification to the manufacture of the final product in the form of news portals and online magazines. The results showed that the design of this virtual laboratory was feasible according to experts and received a positive response from students where most of the students stated that this virtual laboratory helped them to practice journalism needed in the media industry.